Cross-Cultural Adaptation of Indonesian Version of Activities-Specific Balance Confidence Scale for Elderly in Surabaya - Nuruzzaman, Andi; Satyawati, Rwahita; Wulan, Sri Mardjiati Mei (Folia Medica Indonesiana, 2020)
Falling is a major health problem and is also a major cause of morbidity and mortality in the elderly. The more serious consequences of falling on the elderly are the increased risk of injury and fear of falling. Activities-Specific Balance Confidence (ABC) scale is one of the assessment instruments for fear of falling. This instrument is used to assess balance confidence in various ambulation activities. The purpose of this study was to carry out the process of adaptation of the cross cultural ABC English questionnaire to ABC Indonesian. This study was a cross sectional study with participants of five elderly members of the Posyandu Lansia who were in accordance with the inclusion and exclusion criteria. The output is the correlation between the score of ABC English with ABC Indonesian and the score of ABC Indonesian with ABC English Back Translation which are tested at different times. All the question score in the ABC English questionnaire correlated with ABC Indonesian, as well as the Indonesian Language ABC correlated with ABC English back translation, have a significant correlation (r> 0.3). The conclusion of this study is that the ABC English has a close meaning with the ABC Indonesian and the ABC Indonesian has a close meaning with the ABC English back translation. The validity and reliability of the Indonesian version of ABC questionnaire is needed to obtain a valid and reliable questionnaire.